Eunuchs in the Bible - Retief, Francois P.; Cilliers, Louise (Acta Theologica, 2005)
In the original texts of the Bible a “eunuch” is termed saris (Hebrew, Old Testament) or eunouchos (Greek, New Testament). However, both these words could apart from meaning a castrate, also refer to an official or a commander. This study therefore examines the 38 original biblical references to saris and the two references to eunouchos in order to determine their meaning in context. In addition two concepts related to eunuchdom, namely congenital eunuchs and those who voluntarily renounce marriage (celibates), are also discussed.